The Influence of Cropyear on the Yield and Yield Safety of Different Sunflower Hybrids - Dani, Mária; Pepó, Péter (Acta Agraria Debreceniensis, 2005)
The effectiveness of plant production is basically influenced by the ecological, biological and agricultural technical factors. There are many kinds of sunflower hybrids which differres in their adaptability. If we want to increase the efficiency of sunflower production, we have to design different technologies for each hybrid. In the last decade, the range of sunflower hybrids increased exceedingly. This is the reason why we have to do experiments with them and examine what the relationship among genotypes, the environment and the hybrids is. We made our experiments at the Látóképi Experimental Station of the University of Debrecen. We had 57 hybrids in 2001, and 44 in 2002 and 2003. We used only just those hybrids which were planted in every year. In 2001 the months at summer were hot and the distribution of rainfall was extreme. In the beginning of the year 2002, the summer was also hot. During the abscessing period, the temperature was under the 30 years average and the rainless period was typical. In 2003, the temperature was extrame and the rainfall during the growing season was dry. The yield average which was determined after the three years in the very early group averaged 3998,9 kg/ha. The best hybrids were the LG 5385 (4273,3 kg/ha) and the Magóg (4134,4 kg/ha). The early group’s average was 4129,4 kg/ha. The best hybrid was the Astor in the early group. The middle group’s average was 4169 kg/ha and the Zoltán had a better yield than average (4238 kg/ha). In the confectionary group the Iregi szürke csíkos (3579,9 kg/ha) reached the best yield and it is above the average to it’s group (3225 kg/ha). To estimate the results, we used factor analysis. Its results allow us to say that rainfall first and second part of June has a negative influence on yield. Aswith to the yield, yield safety is also important to know, which shows the adaptability of the hybrid. After examining the CV% in the three years we can say that the most stable hybrids were in the very early group Samanta (10,94 CV%) and the LG 5385 (12 CV%) In the early group, the most reliable hybrids were Altesse RM (6,9 CV%) and the Astor (10,8 CV%) and the end in the middle group the Lympil (10 CV%) and in the confectionary group the Birdy (9,8 CV%) and IS 8004 (12 CV%) were the best. After examining yield and yield safety, our conclusions are that in the Hajdúsági löszhát, the very early group LG 5385, early group Altesse RM, middle group Lympil and the parandial group IS 8004 hybrid had the highest yield and the best yield stability.